2021
DOI: 10.3389/fmicb.2021.722229
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Metabolic Remodeling in Mycobacterium smegmatis to Overcome Energy Exigency and Reductive Stress Under Energy-Compromised State

Abstract: Mycobacteria such as Mycobacterium tuberculosis, the causative agent of tuberculosis that annually kills several million people worldwide, and Mycobacterium smegmatis, the non-pathogenic fast-growing mycobacteria, require oxidative phosphorylation to meet their energy requirements. We have previously shown that deletion of one of the two copies of atpD gene that codes for the ATP synthase β-subunit establishes an energy-compromised state in M. smegmatis. Here we report that upon such deletion, a major routing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…These data point toward a role for melH deletion causing NAD(H) depletion, further contributing to an inability to maintain redox homeostasis. Mycobacterium smegmatis Δ atpD exhibits reduced ATP levels, accompanied by elevated levels of ROS and significant alterations in NAD levels, indicating an imbalanced redox state within the cell ( 46 ). This study demonstrated a threefold upregulation of whiB3 in M. smegmatis Δ atpD compared to the WT.…”
Section: Discussionmentioning
confidence: 99%
“…These data point toward a role for melH deletion causing NAD(H) depletion, further contributing to an inability to maintain redox homeostasis. Mycobacterium smegmatis Δ atpD exhibits reduced ATP levels, accompanied by elevated levels of ROS and significant alterations in NAD levels, indicating an imbalanced redox state within the cell ( 46 ). This study demonstrated a threefold upregulation of whiB3 in M. smegmatis Δ atpD compared to the WT.…”
Section: Discussionmentioning
confidence: 99%
“…Several compounds have been identified during the last few years with potential anti-tubular properties and are currently undergoing preclinical and clinical studies like, bedaquiline ( Antoci et al, 2021 ; Chakraborti et al, 2021 ; Patil & Jain, 2021 ; Deshkar & Shirure, 2022 ), PA-824 ( Lenaerts et al, 2005 ; Edwards & Field, 2022 ; Xu et al, 2022 ; Yan et al, 2022 ), and delamanid ( Skripconoka et al, 2013 ; Liu et al, 2018 ; Nasiri et al, 2022 ). Existing drugs have also been modified to repurpose them against TB and they include -riminophenazines ( Valinetz et al, 2020 ; Brunaugh et al, 2022 ), b-lactams ( Moon et al, 2018 ; Story-Roller & Lamichhane, 2018 ; Ur Rahman et al, 2018 ), and oxazolidinones ( Balasubramanian et al, 2014 ; Alghamdi et al, 2020 ; Margaryan et al, 2022 ; Ndukwe et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, leading to increased rates of ATP synthesis and higher metabolic flux at a low energetic expense [56]. In harsh conditions, studies have shown that NDH-1 was downregulated, while ndh genes were upregulated in M. smegmatis [67]. This was also observed in the double deletion of ndh and ndhA which led to the death of the bacteria [55].…”
Section: Nadh Dehydrogenasementioning
confidence: 99%